Effects of the new Swedish strategic Plan for CAP 2023-2027 on proportion of Cultivated Perennial Grasses in Uppsala : aggregate modelling of farmland allocation in Sweden using Positive Mathematical Programming - Bäckelin, Samuel (SLU/Dept. of Economics, 2022)
Changes in compensations and subsidies in the new proposed Swedish strategic plan for CAP will alter farmers’ decisions on the allocation of arable land. This study estimates effects on allocation of cultivated perennial grasses as a result of the proposed abolishment of the current environmental compensation for the named crop. The estimation is based on positive mathematical programming and the study is delimited to Uppsala. Three different calibration approaches for positive mathematical programming are used and the results indicate a decrease in perennial grasses. The results are discussed in regards to environmental goals regarding carbon sequestration and biodiversity established by the EU.